Thank you for the opportunity to help you with your question!

using quadratic formula x= [-b+- sqrt(b^2-4ac)]/2a

here

a=1

b=b

c=9

so

x= [-b+- sqrt(b^2-4(1)(9))]/2(1)

2x+b = sqrt(b^2-36) , 2x+b = - sqrt(b^2-36)

taking square

(2x+b )^2 = b^2-36 , (-2x-b )^2 = b^2-36

4x^2 + b^2 + 4xb = b^2 -36 ,

4x^2+36 = -4xb

b= - [ 4x^2+36/ 4x]

b= - [(x^2+8)/x]

so values of b would be = { - (x^2+8)/x }

if you have any problem in understanding the solution let me know i will be happy to help you and if you have more questions please post it on bids i will help you in less money and will provide you A+ work best of luck :)

Please let me know if you need any clarification. I'm always happy to answer your questions.